2012
DOI: 10.1111/j.1600-0501.2012.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus augmentation with iliac autograft – a health‐economic analysis

Abstract: The cost for a sinus augmentation with iliac surgery exceeds that of a policlinic procedure manifold. Provided that a policlinic operation with local bone, with or without bone substitute, renders an adequate end result, the economic gain would be substantial and post-operative morbidity would be greatly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Autologous bone has been the first grafting material used for this procedure, being regarded for a long time as the gold standard for its osteoconductive, osteoinductive and osteogenetic properties. However, even if autologous bone grafts demonstrated significantly higher new bone formation after sinus augmentation if compared with other bone substitutes (Browaeys et al, 2007 ; Danesh‐Sani et al, 2017 ), their use is associated with major drawbacks such as increased morbidity, limited availability and low dimensional stability over time (Truedsson et al, 2013 ). For these reasons, the possible use and behaviour of alternative biomaterials (including allografts, xenografts, alloplastic grafts, composite grafts, platelet concentrates and growth factors) has been widely investigated in this specific clinical application (Batas et al, 2019 ; Dursun et al, 2016 ; Galindo‐Moreno et al, 2011 ; Monje et al, 2017 ; Stacchi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autologous bone has been the first grafting material used for this procedure, being regarded for a long time as the gold standard for its osteoconductive, osteoinductive and osteogenetic properties. However, even if autologous bone grafts demonstrated significantly higher new bone formation after sinus augmentation if compared with other bone substitutes (Browaeys et al, 2007 ; Danesh‐Sani et al, 2017 ), their use is associated with major drawbacks such as increased morbidity, limited availability and low dimensional stability over time (Truedsson et al, 2013 ). For these reasons, the possible use and behaviour of alternative biomaterials (including allografts, xenografts, alloplastic grafts, composite grafts, platelet concentrates and growth factors) has been widely investigated in this specific clinical application (Batas et al, 2019 ; Dursun et al, 2016 ; Galindo‐Moreno et al, 2011 ; Monje et al, 2017 ; Stacchi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…OHIP-14 has previously been translated into Norwegian and used in a large study (n = 3538) with a calculated Norwegian national norm value [32]. Although previous studies have reported PROMs in relation to bone grafting [9,[33][34][35][36][37][38][39][40][41][42], to our knowledge, only one previous study has systematically assessed impact of donor site harvesting on OHRQoL, where (a) a postoperative lowering of OHRQoL was observed following bone grafting from both intra-oral and extra-oral sites and (b) iliac crest grafts compared to intraoral donor sites had a negative impact on postoperative QoL [37]. Moreover, to our knowledge, only one study has previously assessed the cost-effectiveness of autologous iliac crest grafting [43].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the treatment of complex alveolar bone defects, especially within the aesthetic zone, remains challenging even with respect to both functional and aesthetic restoration. The clinician’s options for treating such defects used to be limited to the use of autologous bone grafts (ABG), with its known drawbacks of increased operation time, costs and complications; increased donor site morbidity and unpredictable resorption [ 1 , 2 , 3 , 4 , 5 ]. In recent years, the advancing development of bone substitute materials has created a set of alternatives with which comparably predictable clinical outcomes can be achieved [ 6 ], as they maintain comparable osteoconductive properties for ABG [ 7 ].…”
Section: Introductionmentioning
confidence: 99%